Resin composition

The resin composition with specific resin blends and additives achieves a low dielectric constant, loss tangent, and high glass transition temperature, addressing the limitations of existing copper-clad substrates for high frequency applications.

JP2025009689AInactive Publication Date: 2025-01-20NANYA PLASTICS CORP

Patent Information

Application Number
JP2023190498
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-06-28
Filing Date
2023-11-08
Publication Date
2025-01-20
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing copper-clad substrates have high dielectric constants and dielectric loss tangents, which are not suitable for high frequency and high speed transmission applications, and they compromise glass transition temperature when low dielectric resins are used to reduce these properties.

Method used

A resin composition comprising a first resin polymerized with styrene, divinylbenzene, and ethylene, a second resin with bismaleimide-modified polyphenylene ether, and a third resin with styrene and butadiene, along with acenaphthylene, achieves a low dielectric constant, low dielectric loss tangent, and high glass transition temperature.

Benefits of technology

The resin composition maintains a low dielectric constant and dielectric loss tangent while significantly increasing the glass transition temperature, enhancing the reliability and flexibility of substrates for high frequency transmission.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025009689000001
    Figure 2025009689000001
  • Figure 2025009689000002
    Figure 2025009689000002
  • Figure 2025009689000003
    Figure 2025009689000003
Patent Text Reader

Abstract

To provide a resin composition having a low dielectric constant, a low dielectric loss tangent, a high glass transition temperature, and a low peeling strength change rate.SOLUTION: A resin composition contains a resin mixture. The resin composition contains a first resin polymerized with a monomer mixture containing styrene, divinyl benzene, and ethylene, a second resin containing a polyphenylene ether resin modified with bismaleimide, a third resin block-polymerized with a monomer mixture containing styrene and butadiene, and acenaphthylene.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composition, and in particular to a resin composition. [Background technology]

[0002] In recent years, with the development of 5G communications, materials for copper-clad substrates have been developed with the aim of lowering their dielectric properties. Currently, the dielectric constant of copper-clad substrates is in the range of about 3.2 to 5.0, which is not favorable for future high-frequency and high-speed transmission applications. Attempts have been made to reduce the dielectric tangent of copper-clad substrates by adding new low-dielectric resins such as polystyrene resins to the resin composition. However, copper-clad substrates made of these new low-dielectric resins lower the dielectric tangent and the glass transition temperature.

[0003] Based on the above, the development of a low dielectric resin composition having a low dielectric constant, a low dielectric loss tangent, and a high glass transition temperature (Tg) is an urgent goal for those skilled in the art. Summary of the Invention [Problem to be solved by the invention]

[0004] The present invention provides a resin composition having a low dielectric constant, a low dielectric loss tangent, a high glass transition temperature, and a low rate of change in peel strength. [Means for solving the problem]

[0005] The resin composition of the present invention includes a resin mixture, which includes a first resin polymerized from a monomer mixture containing styrene, divinylbenzene, and ethylene, a second resin containing a polyphenylene ether resin modified with bismaleimide, a third resin block-polymerized from a monomer mixture containing styrene and butadiene, and acenaphthylene.

[0006] In one embodiment of the present invention, based on the total weight of the resin mixture, the content of the first resin is 10% by weight to 40% by weight, the content of the second resin is 30% by weight to 50% by weight, the content of the third resin is 10% by weight to 30% by weight, and the content of acenaphthylene is 10% by weight to 30% by weight.

[0007] In one embodiment of the present invention, the glass transition temperature of the resin composition is greater than 220°C.

[0008] In one embodiment of the present invention, the resin composition has a peel strength change rate in a reliability test of less than 10%.

[0009] In one embodiment of the present invention, the monomer mixture of the first resin contains 10 mol % to 40 mol % of styrene, 10 mol % to 40 mol % of divinylbenzene, and 10 mol % to 20 mol % of ethylene.

[0010] In one embodiment of the present invention, the first resin has a number average molecular weight of 4,500-6,500.

[0011] In one embodiment of the present invention, the second resin is represented by the following chemical formula: [ka] Here, R is a direct bond, a methylene group, an ethylene group, an isopropylene group, a 1-methylpropylene group, a sulfonylene group, or a fluorenylene group, and n is an integer between 3 and 25.

[0012] In one embodiment of the present invention, the resin composition further comprises a siloxane coupling agent, and the siloxane coupling agent is added in an amount of 0.1 parts by weight to 5 parts by weight based on 100 parts by weight of the resin mixture.

[0013] In one embodiment of the present invention, the resin composition further comprises a flame retardant, and the flame retardant is added in an amount of 10 parts by weight to 50 parts by weight based on 100 parts by weight of the resin mixture.

[0014] In one embodiment of the present invention, the resin composition further contains spherical silicon dioxide, and the content of the spherical silicon dioxide is 30% by weight to 60% by weight of the total of the spherical silicon dioxide, the flame retardant, and the resin mixture. Effect of the Invention

[0015] Based on the above, since the resin composition of the present invention contains a first resin polymerized from a monomer mixture containing styrene, divinylbenzene and ethylene, a second resin containing a polyphenylene ether resin modified with bismaleimide, a third resin block polymerized from a monomer mixture containing styrene and butadiene, and acenaphthylene, a substrate made of the resin composition can achieve a low dielectric constant, a low dielectric tangent, a high glass transition temperature, and a low rate of change in peel strength, thereby improving reliability.

[0016] In order to make the foregoing more easily understandable, several embodiments are described in detail below in conjunction with the drawings. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The embodiments of the present invention will be described in detail below, but these embodiments are merely examples and the present invention is not limited thereto.

[0018] In the present invention, ranges expressed as "one value to another value" are summary expressions that avoid listing all values ​​within the range in the specification. Thus, the recitation of a particular range of values ​​covers any value within that range of values, and any smaller value ranges defined by any value within that range of values, as if each and every value and smaller value range were set forth in the specification.

[0019] A resin composition according to one embodiment of the present invention includes a resin mixture. The resin mixture includes a first resin polymerized with a monomer mixture including styrene, divinylbenzene, and ethylene, a second resin including a polyphenylene ether resin modified with bismaleimide, a third resin block polymerized with a monomer mixture including styrene and butadiene, and acenaphthylene. In some embodiments, the resin composition further includes a flame retardant, spherical silicon dioxide, a siloxane coupling agent, and / or other additives. The various components mentioned above are described in detail below.

[0020] resin composition

[0021] In this embodiment, the resin mixture includes a first resin polymerized from a monomer mixture containing styrene, divinylbenzene, and ethylene, a second resin including a polyphenylene ether resin modified with bismaleimide, a third resin block polymerized from a monomer mixture containing styrene and butadiene, and acenaphthylene.

[0022] First Resin

[0023] In this embodiment, the first resin may be polymerized by a monomer mixture including styrene, divinylbenzene, and ethylene. In the monomer mixture, the molar ratio of styrene, divinylbenzene, and ethylene may be 1:1:1 to 2:2:1. For example, the monomer mixture of the first resin includes 10 mol% to 40 mol% of styrene, 10 mol% to 40 mol% of divinylbenzene, and 10 mol% to 20 mol% of ethylene. In some embodiments, the number average molecular weight of the first resin is 4500 to 6500.

[0024] In some embodiments, the content of the first resin may be 10% to 40% by weight based on the total weight of the resin mixture. The addition of the first resin to the resin composition can help reduce the dielectric constant of the resin composition.

[0025] Second Resin

[0026] In this embodiment, the second resin may include a bismaleimide-modified polyphenylene ether resin. For example, the second resin of the present invention may be the bismaleimide-modified polyphenylene ether resin disclosed in Taiwan Patent Publication I774559, the entire disclosure of which is incorporated herein by reference.

[0027] For example, the chemical structure of a polyphenylene ether resin modified with bismaleimide can be represented by the following chemical formula: [ka] Here, R may be, for example, a direct bond, a methylene group, an ethylene group, an isopropylene group, a 1-methylpropylene group, a sulfonylene group, or a fluorenylene group, and n may be an integer between 3 and 25, and is preferably an integer between 10 and 18.

[0028] The polyphenylene ether resin modified with bismaleimide may be prepared by the preparation method disclosed in Taiwan Patent Publication No. I774559, but the present invention is not limited thereto. The polyphenylene ether resin modified with bismaleimide may be prepared, for example, by other suitable modification methods.

[0029] In some embodiments, the content of the second resin may be 30% by weight to 50% by weight based on the total weight of the resin mixture. Since the chemical structure of the second resin has both a polyphenylene ether main chain and a terminal modified with a highly heat-resistant reactive group (i.e., bismaleimide), the second resin has a relatively low dielectric constant and dielectric loss.

[0030] Third Resin

[0031] In this embodiment, the third resin is block polymerized with a monomer mixture including styrene and butadiene. The third resin is, for example, a styrene-butadiene-styrene block copolymer (SBS). In some embodiments, the third resin may be polymerized with a monomer mixture including 5 mol% to 40 mol% of styrene, 55 mol% to 90 mol% of 1,2-butadiene, and 5 mol% to 30 mol% of 1,4-butadiene. In some embodiments, the number average molecular weight of the third resin may be 3500 to 5500.

[0032] In some embodiments, the content of the third resin may be 10% to 30% by weight, based on the total weight of the resin mixture.

[0033] Acenaphthylene

[0034] Acenaphthylene acts as a crosslinking agent in the resin mixture, and improves the fluidity and glass transition temperature of the resin composition due to its structural properties. In some embodiments, based on the total weight of the resin mixture, the content of acenaphthylene may be 10% by weight to 30% by weight. When the content of acenaphthylene is lower than 10% by weight, the overall effect on the resin composition is not significant, and when the content of acenaphthylene is higher than 30% by weight, the dielectric loss of the resin mixture increases, which is unfavorable for the application of high frequency transmission boards.

[0035] Flame retardants

[0036] In this embodiment, the flame retardant may be a phosphorus-based flame retardant or a bromine-based flame retardant. Specific examples of the flame retardant may include, but are not limited to, Exolit OP 935 (available from Clariant), SPB-100 (available from Otsuka Chemical Co., Ltd.), PX-200 (available from Daihachi Chemical Industry Co., Ltd.), and PQ-60 (available from Jinyi Chemical Industries Co., Ltd.).

[0037] In some embodiments, the flame retardant is added in an amount of 10 parts to 50 parts by weight, based on 100 parts by weight of the resin mixture.

[0038] Spherical silicon dioxide

[0039] In this embodiment, the spherical silicon dioxide can preferably be synthesized by a synthetic method to reduce electrical properties and maintain fluidity and filler properties. The spherical silicon dioxide may have a surface modification of acrylic or vinyl groups, the purity is higher than 99.0%, and the average particle size D50 is about 2.0 μm to 3.0 μm.

[0040] In some embodiments, the content of the spherical silicon dioxide is 30% by weight to 60% by weight of the total of the spherical silicon dioxide, the flame retardant, and the resin mixture.

[0041] Siloxane Coupling Agent

[0042] In this embodiment, the siloxane coupling agent may include, but is not limited to, siloxane.In addition, according to the type of functional group, it can be classified into aminosilane compounds, epoxidesilane compounds, vinylsilane compounds, estersilane compounds, hydroxysilane compounds, isocyanatesilane compounds, methacryloxysilane compounds, and acryloxysilane compounds.

[0043] In some embodiments, the siloxane coupling agent is added in an amount of 0.1 parts by weight to 5 parts by weight based on 100 parts by weight of the resin mixture. The siloxane coupling agent can increase the compatibility and crosslinking degree of the resin composition with the glass fiber cloth and powder.

[0044] Other Additives

[0045] In addition to the above components, the resin composition of the present invention may also include other additives such as initiators, leveling agents, antioxidants, etc. In some embodiments, the initiator may be a peroxide-based initiator.

[0046] In some embodiments, based on 100 parts by weight of the resin mixture, the content of the additive may be, for example, 0.1 parts by weight to 5 parts by weight to achieve the effect of the additive without affecting the overall dielectric properties and adhesion of the resin composition.

[0047] It should be noted that the resin composition of the present invention may be processed into prepregs and / or copper-clad laminates (CCLs) according to actual design requirements. Therefore, the prepregs and copper-clad laminates made of the resin composition of the present invention also have low dielectric constants, low dielectric loss tangents, high glass transition temperatures, and good adhesion properties, and therefore have relatively favorable reliability. More specifically, the prepregs and copper-clad laminates made of the resin composition have a dielectric constant of about 3.0 to 3.1, a dielectric loss tangent of about 0.0015 or less than 0.0015, a glass transition temperature higher than 220°C, for example about 220°C to about 270°C, and a reliability test peel strength change rate of less than 10%, which flexibly responds to environmental changes and improves reliability.

[0048] The resin composition of the present invention will be described in detail below with reference to the following experimental examples, although the following experimental examples are not intended to limit the present invention.

[0049] Example: Preparation of the second resin

[0050] A small molecular weight polyphenylene ether resin material having a number average molecular weight (Mn) of 12,000 or less or 10,000 or less (e.g., Mn=500, 1400, 1600, or 1800) was dissolved in dimethylacetamide, and then potassium carbonate and tetrafluoronitrobenzene were added. The reaction solution was heated to 140°C and reacted for 8 hours, then cooled to room temperature and filtered to remove solids. Methanol / water was used to precipitate the filtrate, and the precipitate was nitrided polyphenylene ether resin. The nitrided polyphenylene ether resin was then dissolved in dimethylacetamide and hydrogenated at 90°C for 8 hours to obtain aminated polyphenylene ether resin. The aminated polyphenylene ether resin was then placed in toluene, and maleic anhydride and p-toluenesulfonic acid were added, and the temperature was raised to 120°C and refluxed, and the reaction was carried out for 8 hours to produce a second resin. The second resin was a polyphenylene ether resin modified by bismaleimide (PPE-BMI).

[0051] Examples 1 to 3 and Comparative Example 1

[0052] In Examples 1 to 3 and Comparative Example 1, a varnish was used using toluene to form a thermosetting resin composition with the resin composition shown in Table 1. This varnish was impregnated into a NAN YA glass fiber cloth (manufactured by NAN YA PLASTICS CORPORATION, cloth type: 1078LD) at room temperature. Then, after drying at 170°C for several minutes (impregnating machine), a prepreg with a resin content of 70% by weight was obtained. Finally, the prepreg was dried at 25 kg / cm 2 Four pieces of prepreg were laminated between two pieces of 35 μm thick copper foil under a pressure of 1000 μm and a temperature of 85° C., held at a constant temperature for 20 minutes, then heated at 3° C. per minute to 210° C. and held at a constant temperature for 120 minutes. It was then slowly cooled to 130° C. to obtain a 0.59 mm thick copper-clad substrate.

[0053] In Table 1, the details of each component are as follows: First resin: purchased from Denka Co., Ltd., model: LDM, Second resin: Use the second resin from the example. Third resin: purchased from Nippon Soda Co., Ltd., model: 1,2-SBS Type-C, Acenaphthylene: purchased from JFE Chemical Corporation. Spherical silicon dioxide: purchased from Sanshiji Company, model: EQ2410-SMC; Flame retardant: purchased from Jinyi Chemical Industries Co., Ltd., model: PQ-60; Siloxane coupling agent: purchased from Dow Corning, model: Z-6030; Initiator: Purchased from ARKEMA Company, Model: Luperox F.

[0054] Evaluation method

[0055] The copper-clad substrates produced in the respective Examples and Comparative Examples were evaluated by the following methods, and the evaluation results were recorded in Table 1.

[0056] Glass transition temperature (° C.): Tested with a dynamic mechanical analyzer (DMA).

[0057] Water absorption rate (%): The sample was heated in a pressure cooker at 120° C. and 2 atm for 120 minutes, and then the weight change before and after heating was calculated.

[0058] Heat resistance (seconds): Samples were heated in a pressure cooker at 120°C and 2 atm for 120 minutes, then immersed in a soldering furnace at 288°C, and the time it took for the sample to burst and delaminate was recorded. If the tin immersion time was longer than 10 minutes without delamination occurring, it was rated as OK. If delamination occurred with an immersion time of less than 10 minutes, it was rated as NG.

[0059] Reliability test - peel strength test: The copper clad laminate (formed by pressing four pieces of semi-cured sheets together) was cut into a rectangular sample 30 mm wide and more than 50 mm long, the surface of the copper clad laminate was etched to leave only a long strip of copper foil 3 mm wide and more than 50 mm long, and a universal tensile tester was used to measure the amount of force (F1) required to peel the initial copper foil from the surface of the insulating layer of the substrate, and the amount of force (F2) required to peel the copper foil after 1000 hours at 85°C and 85% relative humidity. The strength change rate was then calculated as (F2-F1) / F1 x 100%.

[0060] Dielectric constant Dk: The dielectric constant Dk at 10 GHz was measured using a dielectric analyzer HP Agilent E4991A.

[0061] Dielectric loss tangent Df: The dielectric loss tangent Df at 10 GHz was measured using a dielectric analyzer HP Agilent E4991A.

[0062] Resin flow rate: The resin was pressed in a press at 170°C±2.8°C and 200±25 PSI for 10 minutes, melted and cooled, then punched into a disk, and the weight of the disk was accurately measured to calculate the resin flow rate.

[0063] Resin phase separation (slice analysis): Step 1: The copper clad laminate was cut to a size of 1 cm x 1 cm and placed into a mold for resin injection. Step 2: After the resin was dried and fully cured, the samples were ground and polished. Step 3: The samples were analyzed under high resolution microscope such as OM / SEM to see if there was any resin phase separation in the samples.

[0064] [Table 1]

[0065] As can be seen from Table 1, Examples 1 to 3, in which acenaphthylene is contained in the resin composition, have a higher glass transition temperature and maintain low dielectric properties (e.g., low dielectric constant and low dielectric tangent) at high frequencies compared to Comparative Example 1, in which acenaphthylene is not added to the resin composition. Example 1 is. In addition, Examples 1 to 3 have better adhesion than Comparative Example 1 even after 1000 hours at 85°C and a relative humidity of 85%. It can be seen that Examples 1 to 3 exhibit good reliability and are suitable for application to high-frequency transmission substrates.

[0066] In summary, since the resin composition of the present invention contains a first resin polymerized from a monomer mixture containing styrene, divinylbenzene and ethylene, a second resin containing a polyphenylene ether resin modified with bismaleimide, a third resin block polymerized from a monomer mixture containing styrene and butadiene, and acenaphthylene, a substrate made from the resin composition can achieve a low dielectric constant, a low dielectric tangent, a high glass transition temperature, and a low rate of change in peel strength, thereby improving reliability.

[0067] It will be apparent to those skilled in the art that various modifications and variations can be made to the described embodiments without departing from the scope or spirit of the present invention. In view of the foregoing, it is intended that the present invention cover modifications and variations provided they come within the scope of the appended claims and their equivalents. [Industrial Applicability]

[0068] The resin composition of the present invention can be applied to lower the dielectric loss tangent of a copper-clad substrate without lowering the glass transition temperature.

Claims

1. a first resin polymerized from a monomer mixture including styrene, divinylbenzene, and ethylene; a second resin comprising a polyphenylene ether resin modified with bismaleimide; a third resin block-polymerized with a monomer mixture containing styrene and butadiene; Acenaphthylene and A resin mixture comprising Including, Resin composition.

2. Based on the total weight of the resin mixture, the content of the first resin is 10% by weight to 40% by weight, the content of the second resin is 30% by weight to 50% by weight, the content of the third resin is 10% by weight to 30% by weight, and the content of the acenaphthylene is 10% by weight to 30% by weight. The resin composition according to claim 1.

3. The glass transition temperature of the resin composition is higher than 220° C. The resin composition according to claim 1.

4. The resin composition has a reliability test peel strength change rate of less than 10%. The resin composition according to claim 1.

5. the monomer mixture of the first resin comprises 10 mol% to 40 mol% styrene, 10 mol% to 40 mol% divinylbenzene, and 10 mol% to 20 mol% ethylene; The resin composition according to claim 1.

6. The number average molecular weight of the first resin is 4500 to 6500. The resin composition according to claim 1.

7. The second resin has the following chemical formula: 【Chemistry 1】 wherein R is a direct bond, a methylene group, an ethylene group, an isopropylene group, a 1-methylpropylene group, a sulfonylene group, or a fluorenylene group, and n is an integer between 3 and 25; The resin composition according to claim 1.

8. Further comprising a siloxane coupling agent; The siloxane coupling agent is added in an amount of 0.1 parts by weight to 5 parts by weight based on 100 parts by weight of the resin mixture. The resin composition according to claim 1.

9. Further comprising a flame retardant, The flame retardant is added in an amount of 10 parts by weight to 50 parts by weight based on 100 parts by weight of the resin mixture. The resin composition according to claim 1.

10. Further comprising spherical silicon dioxide, The content of the spherical silicon dioxide is 30% by weight to 60% by weight of the total of the spherical silicon dioxide, the flame retardant, and the resin mixture. The resin composition according to claim 9.

Citation Information

Patent Citations

  • Polyphenylene ether resin modified with bismaleimide, method for producing the same, and substrate material for circuit board

    US20230091594A1

  • Resin composition, prepreg, film with resin, metal foil with resin, metal-clad laminate and wiring board

    WO2020017399A1

  • Curable composition and cured article thereof

    WO2021112088A1

Cited By

  • Resin composition, and prepreg, resin-coated film, resin-coated metal foil, metal-clad laminate, and wiring board each obtained using same

    WO2025142541A1

  • Curable resin composition and cured product thereof

    WO2026177077A1